TI_GERICHTE 35.2017.105 vom 22. Januar 2018 , Radiologo. No infortunio. No lesione parificata. Ricorso respinto - TI Tribunale d'appello (2018)
Radiologo. No infortunio. No lesione parificata. Ricorso respinto